The influence of health education to improve community knowledge of basic life support procedure in Dlanggu district, Mojokerto regency, Indonesia - Nuris Kushayati; Linda Presti Fibriana; Luthfiah Nur Aini; Edy Siswantoro; Nasrul Hadi Purwanto; Kurnia Indriyanti Purnama Sari; Widya Anggraeni (AOSIS, 2019)
Basic Life Support (BLS) is an attempt to sustain life when a person experiences a life-threatening situation. BLS should be given to survivors with cardiopulmonary arrest. Ignorance of help and incompetent BLS management of a helper often occur in real cases in the field. This study aimed to determine the effect of health education on basic life support to the level of public knowledge. This research design used Pre- Experimental Design, with One Group Pretest-Posttest Design method. The population of this research is the community of Dlanggu District, Mojokerto Regency. The sample was taken as many as 59 respondents. The sampling method used is Probability type Simple Random Sampling. The data were collected using a questionnaire. The data was analyzed by using Wilcoxon Signed Rank Test with a significance level <0.05. The results showed a significance value of 0.000 (p<0.05), thus it can be concluded that there were significant differences before and after the provision of health education about BLS procedures.